Quantification of Redox Sites during Catalytic Propane Oxychlorination by Operando EPR Spectroscopy. Issue 7 (15th December 2020) - Zichittella, Guido; Polyhach, Yevhen; Tschaggelar, René; Jeschke, Gunnar; Pérez‐Ramírez, Javier
Abstract: Identification and quantification of redox‐active centers at relevant conditions for catalysis is pivotal to understand reaction mechanisms and requires development of advanced operando methods. Herein, we demonstrate operando EPR spectroscopy as an important technique to quantify the oxidation state of representative CrPO4 and EuOCl catalysts during propane oxychlorination, an attractive route for propylene production. In particular, we show that the space‐time‐yield of C3 H6 correlates with the amount of Cr 2+ and Eu 2+ ions generated over the catalysts during reaction. These results provide a powerful strategy to gather quantitative understanding of selective alkane oxidation, which could potentially be extrapolated to other functionalization approaches and operating conditions. Abstract : The oxidation state of state‐of‐the‐art CrPO4 and EuOCl catalysts was quantified and correlated with the productivity of propylene during propane oxychlorination by operando EPR spectroscopy.